Membrane technology: obtaining whey protein (2019)
The whey proteins have acquired great importance due to their nutritional and technological functionality. In the present review, we studied the use of Ultrafi ltration (UF) applied to the separation of proteins and peptides from whey. It was found that the UF is one of the best alternatives. However, to achieve better results it is necessary to: accompany other membrane technologies (microfiltration,nanofi ltration, electrodialysis, diafiltration), select the type of UF membrane to be used, and adjust the conditions of transmembrane pressure, pH and temperature.